2021
DOI: 10.4103/njcp.njcp_501_20
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dental anxiety on surgical time of mandibular third molar disimpaction

Abstract: Background: Dental treatment of anxious patients induces stress due to the patients' expectation of pain. This may prolong treatment due to such patients' inability to cooperate during treatment. Aim: The aim of the study was to determine the effect of dental anxiety on surgical time of mandibular third molar (M3) disimpactions at a Nigerian hospital. Subjects and Methods: A prospective study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…20 In another study on dental anxiety, 36.2% of respondents reported being mildly anxious, 57.8% reported being moderately anxious, and 6.0% reported being highly anxious. 21 The present findings also align with previous studies that reported that the incidence of dental anxiety is not gender related. 22,23 Also, Folayan et al 22 reported that gender alone could not substantially determine dental anxiety, but it may contribute when combined with other factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20 In another study on dental anxiety, 36.2% of respondents reported being mildly anxious, 57.8% reported being moderately anxious, and 6.0% reported being highly anxious. 21 The present findings also align with previous studies that reported that the incidence of dental anxiety is not gender related. 22,23 Also, Folayan et al 22 reported that gender alone could not substantially determine dental anxiety, but it may contribute when combined with other factors.…”
Section: Discussionsupporting
confidence: 92%
“…The findings also supported the hypothesis that the influence of gender, age, SES, and parental education on schoolchildren's dental anxiety is not statistically significant. Although some studies indicated that gender predicts dental anxiety following their report that dental anxiety was higher in adult females than males, 7,12,[14][15][16][17]21 one study showed that no gender disparity exists in dental anxiety levels among children. 22 In contrast to some research that found that participants' age was a contributing factor to differences in dental anxiety scores, 7,11,12,15 other studies found the opposite, 8,24 which is consistent with our current findings regarding the relationship between age and dental anxiety in schoolchildren.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when subjected to excessive pressure, its rotational speed decay is greatly improved, and it basically maintains a constant speed to cut dental hard tissues, which greatly reduces the operation time; at the same time, the rate of temperature increase is greatly improved during long time and overload work, and the service life of the electric motor is the life of the electric motor is prolonged and failure is reduced. (MDAS) [12] was used to evaluate the anxiety of patients during ① Pain: Visual Analogue Score (VAS) was used to quantify [13] the degree of postoperative wound pain, VAS value of 0-10, 0 indicates complete painlessness , 10 indicates unbearable pain, and the larger the number, the more severe the pain.…”
mentioning
confidence: 99%
“…Based on the known advantages of UBK and DEM, we assume that the operation can relieve pain, swelling, limited opening and reduce the incidence of postoperative (MDAS) [12] was used to evaluate the anxiety of patients during ① Pain: Visual Analogue Score (VAS) was used to quantify [13] the degree of postoperative wound pain, VAS value of 0-10, 0 indicates complete painlessness , 10 indicates unbearable pain, and the larger the number, the more severe the pain.…”
mentioning
confidence: 99%